Post-processed dataset: An ocean memory approach for analysing decadal variability in the North Atlantic Ocean - Khatri, Hemant (Zenodo, 2024)
The dataset contains Python scripts and pre-processed data from selected CMIP6 models and observations. These were used to examine how the North Atlantic Oscillation affects decadal variations in the North Atlantic Ocean. An ocean memory approach, combining heat budget analysis with the Green's function method, is proposed.